Association Between Endometriosis and Subsequent Risk of Sjögren’s Syndrome: A Nationwide Population-Based Cohort Study - Chao, Yung-Hsiang; Liu, Chin-Hsiu; Pan, Yu-An; Yen, Fu-Shun; Chiou, Jeng-Yuan; Wei, James Cheng-Chung (Frontiers in Immunology, 2022)
Objective The relationship between endometriosis and the ensuing risk of Sjögren’s syndrome has remained unclear. This study aims to present epidemiological evidence for this connection. Methods This is a retrospective cohort study of endometriosis patients (ICD-9-CM 617.0-617.9 and 621.3) and matched comparison group between 2000 and 2012 in the National Taiwan Insurance Research Database. After age matching, we analyzed the association between endometriosis and Sjögren’s syndrome (ICD-9-CM 710.2). We used the Cox proportional hazard model to examine the hazard ratio of incidental Sjögren’s syndrome. Subgroup analyses on age, comorbidities, and disease duration were also performed. Results A total of 73,665 individuals were included in this study. We identified 14733 newly diagnosed endometriosis patients and 58,932 non-endometriosis comparison group. The adjusted hazard ratio (HR) for incidental Sjögren’s syndrome was 1.45 (95% confidence interval CI=1.27-1.65) in the endometriosis group, compared to the non-endometriosis comparison group. In subgroup analysis, the adjusted HR was 1.53 (95% CI=1.25-1.88) in the age group of 20-39 and 1.41 (95% CI =1.18-1.68) in the age of 40-64. Time-vary analysis showed that endometriosis who have a follow-up time of fewer than five years (adjusted HR=1.57, 95% CI=1.32-1.87) have a significantly highest risk of having subsequent Sjögren’s syndrome. Conclusion This population-based cohort study indicated that having a history of endometriosis puts patients at an increased risk of getting Sjögren’s syndrome afterward, especially in the age group of 20-39 and within the first five years after the diagnosis of endometriosis. Clinicians should recognize this possible association in managing endometriosis or Sjögren’s syndrome patients.